Menyokong Tenaga Kerja: Fenomena Waithood dan Kerja Perawatan Tak Berupah dalam Perspektif Reproduksi Sosial - Khairiyah, Alfiatul; Thohir, Muhammad Aminullah (Yayasan Jurnal Perempuan, 2023)
The construction of unpaid care work as the responsibility of women has contributed to the emergence of the postponing marriage phenomenon (waithood) among youth, especially women. On the other hand, care work is an integral part of the reproductive workforce, related to productive work. Furthermore, care work also contributes to reproducing the workforce in serving the interests of capital accumulation. The mechanization of women’s roles in creating a workforce surplus makes women work excessively and hinders economic access. It argues that the financial pressures and the burden of work indirectly lead to the delayed marriage phenomenon. This financial pressure and the burden of care work indirectly contribute to the postponement of marriage. This study adopts a perspective of Social Reproduction Theory by utilizing qualitative research methods and a literature study approach. This study analyzes the relationship between capitalism, care work, and the recent phenomenon of waithood. The results indicate that women have been supporting the workforce through their care work, and this occurs systemically as a consequence of the capitalist system, which has led to the postponement of women’s marriages.